Cytogenetic and FISH Analyses of the Abortus Materials: A Useful Approach Towards Genetic Counseling for the Couples with Recurrent Spontaneous Abortions - Akın, Haluk; Yüce, Hüseyin (Fırat University, 2004)
Objective: The cytogenetic analyses of the abortus material provide important information about the recurrence risks and possible management for the couples with recurrent spontanous abortions. The methods of cytogenetic analyses depend on primarily cell culture that has relatively higher (10- 40%) failure. Since the most common chromosomal abnormalities in abortus materials are numerical chromosomal abnormalities; we evaluated the compatibility of the karyotypes and interphase-Fluoresan in situ Hybridization (FISH) results and the predictive value of interphase FISH technique in cases with tissue culture failure. Materials & Methods: Interphase-FISH slides were prepared using touch preparation protocol from fresh tissue samples to eliminate the collagenase procedure. FISH procedure was carried out using specific probes for centromeric 13, 16, 18 and 21. At least 100 interphase cells for each slides were detected. Results and Conclusion: Chromosomal abnormality incidence of our study (45.5%) seems to be compatible with literature. It is founded some numerical aberrations (chromosomal abnormalities) as 18.18%autosomal trisomies, 13.64% triploidies, 4.50% monosomies and 9% mosaicism in cases. Two out of twenty eight abortus materials with tissue culture failure were revealed trisomies by FISH. However, the tissue culture failure incidence of this study (56%) is higher than the reported incidences (10-40%). This shortcoming could be diminished by the improvement of the tissue procurement and transportation conditions for culture. With this approach, supportive data will be accumulated and utilized for future epidemiological studies by concurrent FISH preparations and culture set up. ©2004, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Abortus materyalinin sitogenetik analizleri, tekrarlayan abortuslu çiftler için tekrar riski ve çiftlere verilecek olan genetik danışmanlık hakkında önemli bilgiler sağlar. Primer hücre kültürüne dayalı olan sitogenetik analiz metodları nispeten yüksek sayılabilecek bir oranda başarısızlık gösterir (%10-40). Sayısal kromozom anormallikleri, abortus materyallerindeki en yaygın kromozomal anormallikler olduğu için karyotip ve interfaz- Floresan in situ Hibridizasyon (FISH) sonuçlarının uyumluluğu ve doku kültürü başarısızlığı gösteren vakalarda interfaz FISH tekniğinin kullanılabilirliği değerlendirildi. Gereç ve Yöntem: İnterfaz FISH preparatları kollajenaz prosedürünü ortadan kaldırmak için taze doku örneklerinden dokundurma yöntemi kullanılarak hazırlandı. FISH çalışmaları 13, 16, 18 ve 21'in sentromerine spesifik problar kullanılarak yapıldı. Her bir preparat için en az 100 interfaz hücresi değerlendirildi. Bulgular ve Sonuç: Bu çalışmadaki kromozomal anomali insidansı %45.5 olup literatür ile uyumludur. Vakaların %18.8'inde otozomal trizomiler, %13.64'ünde triploidiler, %4.50'sinde monozomiler ve %9'unda mozaik sayısal kromozomal anomaliler bulundu. Doku kültürü başarısızlığı olan 28 düşük materyalinin ikisinde FISH tekniği ile trizomi tanımlandı. Bununla birlikte doku kültür başarısızlığı insidansı (%56), rapor edilmiş insidanslardan (%10-40) daha yüksekti. Bu başarısızlık farkı, kültür için doku temini ve transport koşullarının iyileşmesi ile azaltılabilir. Bu yaklaşımla, destekleyici bilgiler toplanacak ve bunun sonucunda FISH preparasyonları ile kültür kurma arasındaki uyum, gelecekteki epidemiyolojik çalışmalarda faydalı olacaktır. ©2004, Fırat Üniversitesi, Tıp Fakültesi
Abortus Materyallerinin Sitogenetik ve FISH incelemeleri: Rekurren Spontan Abortuslu Çiftlerin Genetik Danışmanlığına Yönelik Yararlı Bir Yaklaşım